A Case Study of Low Compressive Strength of Concrete Containing Fly Ash in East Java Indonesia. (2015) - Darmawan, M. Sigit; Bayuaji, Ridho; Husin, Nur Ahmad; Chomaedhi; Saud, Ismail
Abstract: The utilization of fly ash (FA) into concrete has become a common practice in ready mix concrete production throughout the world, including Indonesia. The inclusion of this by product material into concrete has two main advantages: decreasing cost of material by reducing cement content and reducing waste produced from power plant operation. Despite almost two decades of experience and application, low compressive strength of concrete containing FA often occurs in construction projects in Indonesia. This paper describes one case of low compressive strength of concrete containing FA in a project located in East Java. During project construction, it was found from routine compressive test of concrete cylinders that the 28 days design strength was not achieved. Steps and measure taken following this incident are fully described. Non-destructive and destructive concrete test were employed to gain more data from concrete structures already casted with this mixture. Finally, possible cause of low compressive strength are identified and solutions are given to solve this problem.